On the effect of deformation in a wing model on the correlation of the lift slope - Gutiérrez-Castillo, Paloma; Durán-Venegas, Eduardo; Konovalov-Shishov, Nikita; Del-Pino-Peñas, Carlos Manuel (My University, 2023)
Deformed wing models with a NACA0012 airfoil are analyzed experimentally in a wind tunnel at the University of Malaga. Measurements show the influence of the level of the deformation on the lift coefficient and, therefore, on the slope of the lift coefficient versus the angle of attack. In general, the deformation increments the value of the lift coefficient. This gain is more noticeable for higher wind models (or higher aspect ratios) and when the wing models are tested at higher Reynolds numbers. We estimated the value of the lift slope with a correlation as a function of Reynolds number and aspect ratio, showing an excellent agreement.
Keywords: Mecánica de fluidos; Lift slope